Comparative study of the academic success in the subject of Chemistry I at Universidad Estatal a Distancia (UNED) and the formation of students in Costa Rican secondary education. (Revista Electrónica Calidad en la Educación Superior, 2018)
The teaching of chemistry at secondary level have shown deficiency in the quality of the students' academic training in this subject, which leads to a low performance in the initial course of Chemistry I, included in every science-based university career in Costa Rica. At the Universidad Estatal a Distancia (UNED), six careers include in their curriculum the subject. The 2010-2017 period shows a performance of 20.2% approval, 62.2% failure and 17.6% withdrawal in this subject. During the III quarter academic period 2017, a survey developed in Google Sites® was applied through the Moodle platform of the UNED, in order to obtain socio-demographic, academic and performance data in the subject of chemistry. The qualitative and quantitative data was simultaneously analyzed taking as a reference the mixed method of concurrent triangulation design. The analysis of the attitudinal factor, the teaching-learning at secondary level factor and the teaching-learning at university level factor, indicate an important relationship between the deficient academic bases in level chemistry and the high percentages of failure at university level chemistry.